Implementasi Wireless Sensor Network Untuk Otomatisasi Suhu Ruang Dan Kelembaban Tanah Pada Greenhouse Berbasis Web Server - Adnantha, Yogha Arieka; Kusuma, Wahyu Andhyka (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2018)
Along with the increasing population of Indonesia which is also followed by the increasing rate of urbanization in the industrial sector, certainly affects the reduced agricultural sector to increase food needs. Greenhouse can be one solution to solve this problem, by utilize greenhouse our enviroment can be controlled and also protect the plants from outside interference. During this condition is still done manually both to measure the temperature or watering the plants. In this study the author developed a system to monitor and automate room temperature and soil moisture in greenhouse by utilizing Wireless Sensor Network (WSN) technology. The system consists of 1 node temperature and humidity chamber and 1 node of greenhouse soil moisture where each node is composed of arduino uno as its microcontroller, ESP8266 as Wi-Fi module, sensor, and relay. The results of monitoring and automation data will be sent to the web server by wireless, to make it easier for greenhouse farmers and monitoring their greenhouse. The results of this study can be found that the system is able to monitor and perform automatic control of temperature decrease, when the temperature reaches more than 28C and able to increase soil moisture automatically when the soil moisture is less than 40%, in addition by using ESP8266 data monitoring and automation results can be sent to the web server but based on the test results obtained that the maximum range of data transmission is 50 meters from the node to the access point.